Cinematography. 8 mm film. Sound. Specification for recorded characteristics for magnetic sound record on 8 mm Type S motion-picture prints and full-coat magnetic film perforated 8 mm Type S Part 1.4.6, (26th February 1982) - British Standards Institution,
No abstract available